RESOURCE BASED-VIEW(RBV) DAN KAPABILITAS INOVASI UKM DI KOTA MADIUN - Laurens Paulus, Ardianus (Widya Warta, 2020)
The Small and Medium Enterprises (SMEs) sector is one of the backbone of the Indonesian economy and there are still many weaknesses, especially in small cities and underdeveloped areas.Many SMEs engaged in the same industry, however there are those who are successful and  not successful.The study analyzes the effect of resource-based views consisting of human capital, structural capital and relational capital on the innovation capabilities of SMEs in the Madiun  City.  The  analysis  unit  is  the  owner  of  SME’s  business  with  the  sampling  of  120 respondents. The sampling technique was purposive sampling and the surveys was taken by using  questionnaires.  Multiple  regression  analysis  was  employed  to  process  the  data.This study provides results that RBV theory that consist of human capital, structural capital and relational capital has no impact on the innovation capabilities of SMEs in Madiun.